2021
DOI: 10.1097/corr.0000000000002042
|View full text |Cite
|
Sign up to set email alerts
|

How Did Coronavirus-19 Impact the Expenses for Medical Students Applying to an Orthopaedic Surgery Residency in 2020 to 2021?

Abstract: Background Orthopaedic surgery is one of the most competitive specialties for residency applicants. For the 2021 residency match, the coronavirus-19 pandemic introduced complexity for programs and applicants because away rotations were limited and in-person interviews were cancelled. This may have changed the landscape in terms of expenses for candidates in important ways, but this topic has been insufficiently studied. Questions/purposes Given that in 2021, students did not attend away rotations and all inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 32 publications
1
18
0
Order By: Relevance
“…Although this rise can be partially attributed to the ongoing growth for several years, the growth during the 2019 to 2020 application cycle was significantly higher than that reported between previous cycles (p < 0.05). In our opinion, this significant rise in the annual growth in the number of applications can be attributed to the virtual nature of interviews that cycle that has slashed a huge financial burden 20 . In addition, we theorize the ease of scheduling and stacking virtual interviews from coast to coast has also contributed to this growth.…”
Section: Discussionmentioning
confidence: 99%
“…Although this rise can be partially attributed to the ongoing growth for several years, the growth during the 2019 to 2020 application cycle was significantly higher than that reported between previous cycles (p < 0.05). In our opinion, this significant rise in the annual growth in the number of applications can be attributed to the virtual nature of interviews that cycle that has slashed a huge financial burden 20 . In addition, we theorize the ease of scheduling and stacking virtual interviews from coast to coast has also contributed to this growth.…”
Section: Discussionmentioning
confidence: 99%
“…These findings highlight the significant savings that applicants experienced due to the implementation of virtual interviews and the cancellation of away rotations, which is consistent with previous findings from otolaryngology 12 , 13 and other surgical subspecialties. 14 , 15 …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of otolaryngology applicants have used the National Residency Match Program data to show a significant increase in the number of applicants matching at or close to home during the years of the COVID-19 pandemic, likely due to the limitations of away rotations and in-person interviews [ 11 - 12 ]. Studies were performed with dermatology and orthopedics applicants looking more specifically at the change in costs related to the COVID-19 pandemic [ 9 , 13 ]. These studies both found that virtual interviews and a limited number of away rotations significantly reduced the cost of the application process, with applicants from the Western United States medical schools potentially saving the most [ 9 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies were performed with dermatology and orthopedics applicants looking more specifically at the change in costs related to the COVID-19 pandemic [ 9 , 13 ]. These studies both found that virtual interviews and a limited number of away rotations significantly reduced the cost of the application process, with applicants from the Western United States medical schools potentially saving the most [ 9 , 13 ]. To our knowledge, this is the first comparative cost analysis study conducted to evaluate the effect of the pandemic on otolaryngology applicants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation